Projeto educativo da Rede Salesiana de Escolas: análise do processo de implantação em escolas do estado de São Paulo - Silva, José Adão Rodrigues da (2007)
The purpose of the present work is to analyse the process of the educational project development regarding Rede Salesiana de Escolas , aiming at identifying the limits and advancements related to the school professionals participation and the changes that followed the process. The proposition of Rede Salesiana de Escolas educational project is in accordance with the principles of Lei de Diretrizes e Bases da Educação Nacional LDB and Parâmetros Curriculares Nacionais PCNs attached to salesian pedagogy to ensure an excellent school education to its students. In order to watch the development steps of that educational project, we appointed interviews with school principals, pedagogical counselors and teachers from different salesian schools in São Paulo Estate. The analysis was based on qualitative approach of education research, aiming at identifying the professionals perception over the process of development. The collected data from the interviews showed differences towards the professionals participation in the project construction whereas they showed similar perception concerning the changes that followed the process